2018
DOI: 10.1007/s00276-018-1974-8
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and anatomical features of ethmomaxillary sinus and its differentiation from surrounding air cells

Abstract: EMS was not a rare variation that should be careful identification during endoscopic sinus surgery. Accurately confirming EMS is the key to completely opening and removing lesions in the MS and EMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 16 publications
3
25
0
Order By: Relevance
“… 9 18 19 Previous studies have reported the prevalence of ANC (6.4-98.5%), SOEC (2.6-64.6%), Haller cell (4.6-60.0%), Onodi cell (8.0-65.3%), and EMS (0.7-8.2%), with substantial variation in different populations. 18 19 20 21 22 23 24 25 26 27 A comparison of the prevalence of variations in the present cohort showed that the prevalence of ANS, SOEC, Haller cell, and Onodi cell was well within the reported limits of occurrence. Additionally, the prevalence of SOEC (19.4%) corroborates previous findings that SOEC is less frequently detected in East Asians than in Caucasians.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“… 9 18 19 Previous studies have reported the prevalence of ANC (6.4-98.5%), SOEC (2.6-64.6%), Haller cell (4.6-60.0%), Onodi cell (8.0-65.3%), and EMS (0.7-8.2%), with substantial variation in different populations. 18 19 20 21 22 23 24 25 26 27 A comparison of the prevalence of variations in the present cohort showed that the prevalence of ANS, SOEC, Haller cell, and Onodi cell was well within the reported limits of occurrence. Additionally, the prevalence of SOEC (19.4%) corroborates previous findings that SOEC is less frequently detected in East Asians than in Caucasians.…”
Section: Discussionsupporting
confidence: 60%
“… 27 28 However, this study identified a higher prevalence of EMS (16.5%) than has been previously reported. 22 This finding may be due to population differences among studies. Thus, future studies in similar Southern Chinese cohorts are now needed to confirm this observation.…”
Section: Discussionmentioning
confidence: 99%
“…But the definition of EMS and RMC was indistinct and ambiguous. Several points on the differentiation of EMS and RMC had been presented by Liu et al 19 : (1) drainage channel: On the coronal plane of the CT scan, the EMS has clear drainage channel, whereas RMC do not. This is the most important identification point (Figure 2A); (2) relation with the MS: EMS enters into the MS, whereas RMC is out of the MS, so the septum between EMS and orbit is the superior wall of maxillary while that between RMC and orbit is the wall of RMC, but this point sometime is difficult to be distinguished on CT scans; (3) pneumatization range: The pneumatization range of RMC is often limited to the infraorbital region and behind the MS, but the pneumatization range of EMS shows great variability, which can expand downward, even extending to the entire posterior wall of the MS, the inferior wall of the EMS can also appeared in the alveolar process.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with chronic nasal obstruction, because the nasal structure varies greatly among different individuals, 25 , 26 it is necessary to individually evaluate the abnormal nasal structure according to different patients. When a patient has many structural abnormities at the same time, how can the structure of surgical intervention be chosen?…”
Section: Septoplasty Is Only One Of the Surgical Components For The T...mentioning
confidence: 99%